Female intrasexual competitiveness interacts with body mass index to predict willingness to use a risky diet pill - Arnocky, Steven; Brennan, Hillary; Denomme, Brittany; Davis, Adam C. (Frontiers in Psychology, 2023)
Previous research has highlighted the putative role of intrasexual competition (IC) in predicting women’s body dissatisfaction, weight loss effort, and, at its extreme, eating disorders. However, extant research reporting on these links is limited by its exclusion of potential confounds, including psychopathologies such as depression. Moreover, it is presently unclear whether women higher in body mass index (BMI) may be more prone to the influence of IC in taking dieting risks. To address these gaps in the literature, 189 young adult women completed measures of IC, depressive symptoms, willingness to use a risky diet pill, and had their height and weight measured. Results showed that IC interacted with BMI to predict willingness to use a risky diet pill, such that women high in both IC and BMI were most likely to take the risky diet pill. Results suggest that links between IC and dieting risks may be moderated by women’s BMI, and that these links hold when considering depressive symptoms.